On the influence of the cooling rate on the martensitic transformation of Ni–Mn–Sn Heusler alloys. (15th March 2016) - Kalbfleisch, Anne-Sophie; Matthews, Guillaume; Jacques, Pascal J.
Abstract: The present study deals with Ni–Mn–Sn compounds that present large magnetocaloric effect through a first-order magnetostructural transition. The influence of the processing path on the martensitic transformation temperatures was scrutinized by calorimetric measurements. It is shown that the increase of the cooling rate from the annealing temperature brings about a decrease of the martensitic transformation temperatures. All transformation temperatures were also higher in the case of powdered samples compared to bulk samples. A small variation of the degree of atomic order was highlighted and could be linked to the observed phenomena. Graphical abstract: